Reestructuración de procesos de la empresa restaurant.pe para elevar la permanencia de clientes - Icochea Aguirre, Miguel Angel (2020)
Business in the restaurant sector in Peru are increasing, this implies that companies seek to optimize their processes to provide a better quality service to their customers. Restaurant.pe is a company that provides its clients with software focused on the administration and operation of the premises, providing information remotely and in real time to the owners. Being a growing Start-up, Restaurant.pe did not have defined areas or processes, which generated loss of information through the contact channels for its customers, causing them to make the decision to abandon the service provided by the company, generating losses in monthly billing. For this reason, to identify the recurring reasons that led clients to make that decision, methods such as the Ishikawa diagram were used, generating the creation of new control tools such as inspection, installation and customer monitoring checklist, among others. These tools allowed Restaurant.pe to carry out a restructuring of processes in the support and customer service areas respectively, thereby increasing customer retention in the company and improving its monthly billing.